Utilization of Casertana pig to produce traditional typified labelled salami. Data at slaughtering and jointing of carcass - Gigante G.; Barone C.M.A.; Castellano N.; Colatruglio P.; Rossetti C.E.; Occidente M.; Zullo A.; Matassino D. (5. International Symposium on the Mediterranean Pig, 2007)
The investigation was carried out on 15 castrated males and 15 entire females of Casertana pig reared according to the intensive technology at the experimental farm of ConSDABI. The carcasses were chilled for 3 days at 2-4°C and dissected into cuts, according to the Napolitan method. The data were grouped into 3 classes of live weight: 130-160 kg, 161-190 kg, >190 kg. The most important results showed: (i) an expected significant increase of carcass weight from first to second to third weight class, as well as hot dressing percentage, only from 2nd to 3rd class though (P<0.001); (ii) a higher percentage of meaty cuts in pigs belonging to 1st class in comparison to 3rd (P<0.05) but a similar percentage of fatty (7.56 vs 8.69) and bone (6.23 vs 6.15) cuts and (iii) females have a higher proportion of leg ham (P<0.05) and overall meat cuts (P<0.01), than castrated males.
5. International Symposium on the Mediterranean Pig, 2004/09/16-19, Tarbes (France)